High prevalence of “Candidatus Rickettsia amblyommii” in Amblyomma ticks from a Spotted Fever Endemic Region in North Argentina - Mastropaolo, Mariano (2016)
Ticks from an endemic Spotted Fever region in Argentina were analysed by PCR for Spotted Fever Group Rickettsiae. DNA of “Candidatus Rickettsia amblyommii” was found in 21.3% of Amblyomma hadanii and in 44.0% of A. neumanni. Amblyomma sculptum (formerly A. cajennense) and Haemaphysalis juxtakochi were negative for rickettsial DNA. DNA of Rickettsia rickettsii, the etiological agent of the clinical cases reported within the studied region was not detected in the analysed sample.